A previously unrecognized example of the shock-induced breakdown of biotite to garnet from the Steen River impact structure, Canada - Walton, Erin L.; Sharp, Thomas G.; Hu, Jinping; Tschauner, Oliver (My University, 2016)
Shock metamorphic effects from quartz and feldspar have been studied in detail, and to a lesser extent olivine and pyroxene. Less is known about how shock is manifest in other minerals such as double chain inosilicates, phyllosilicates, carbonates and sulfates. In this study, we investigate shock in crystalline basement rocks from the Steen River impact structure (SRIS), a 25-km diameter complex crater in NW Alberta, Canada.
Presented on August 7-12, 2016 at the Annual Meeting of the Meteoritical Society held at the Henry Ford Building in Berlin, Germany.
Keywords: shock; crystalline basement rocks; impact structures